A Pyridine Diketopyrrolopyrrole-Grafted Graphene Oxide Nanocomposite for the Sensitive Detection of Chloramphenicol by a Direct Electrochemical Method - Lingpu Jia; Juan Hao; Long Yang; Jun Wang; Lijuan Huang; Kunping Liu (Nanomaterials, 2023)
A novel direct electrochemical sensor, based on a pyridine diketopyrrolopyrrole/graphene oxide nanocomposite-modified glass carbon electrode (PDPP/GO/GCE), was developed herein for chloramphenicol (CAP) detection. In this research, PDPP was grafted onto GO by C-N bonds and π-π conjugation, which were synergistically confirmed by Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy. The morphology study shows that PDPP was uniformly dispersed on the GO in the form of particles. The constructed PDPP/GO/GCE showed the strongest response signal to CAP in the evaluation of electrocatalytic activity by cyclic voltammetry compared to that of GO-modified and unmodified GCE, revealing that the introduction of PDPP can effectively improve the electrocatalytic activity of sensors. Moreover, PDPP/GO/GCE had a noticeable current signal when the concentration of CAP was as low as 0.001 uM and had a wide line range (0.01–780 uM) with a low limit of detection (1.64 nM). The sensor properties of the as-obtained PDPP/GO/GCE involved anti-interference, reproducibility, and stability, which were also evaluated and revealed satisfactory results.